Traders and agri-food value chain resilience: The case of maize in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Myanmar has experienced a sequence of dire crises beginning in 2019 including the unexpected closure of a principal trade route, COVID-19 lockdowns and travel restrictions, and a military coup leading to years of disruptions in the banking and transport sectors, inflation, and conflict. Yet, through these cascading shocks Myanmar’s maize sector experienced robust growth in production and exports. This paper examines the reasons underlying this apparent paradox and our findings contribute to the small but growing literatures on agri-food value chain (AVC) resilience and adaptation by traders. Strengthening the resilience of AVCs to shocks has important implications for welfare in developing countries and is increasingly drawing attention from policymakers and development partners. Using data from several sources including rare panel data sets of traders and farmers, and key informant interviews, we show that crop traders have been critical to the resilience of the maize value chain in Myanmar during this turbulent period. Maize traders performed three key functions contributing to resilience: (i) market discovery when primary trade routes were closed; (ii) overcoming transportation disruptions and bank closures to move maize from the farmgate to local and export markets; (iii) maintaining flows of credit to farmers throughout the crises in the form of selling inputs on credit and lending cash, thereby injecting much needed liquidity at times of incredible uncertainty, disruptions in the banking sector, and rising input prices.